A water-soluble PEGylated RGD-functionalized bisbithiophenyl diketopyrrolopyrrole as a photoacoustic sonophore. Issue 5 (24th April 2018) - Repenko, Tatjana; Rix, Anne; Haehnle, Bastian; Lederle, Wiltrud; De Laporte, Laura; Kuehne, Alexander J. C.
Abstract : Here we present a water-soluble molecular photoacoustic probe based on diketopyrrolopyrrole for conjugation with biomolecular targeting motifs. Abstract : Photoacoustic imaging presents an innocuous imaging modality with good penetration depth and resolution. To use this modality for detection and imaging of pathological sites, new imaging probes need to be developed to enhance the contrast over endogenous sonophores. These contrast agents should specifically bind to the site of interest, be non-toxic and be cleared renally if applied intravenously. Small organic dyes with absorption in the near infrared spectrum often exhibit good photoacoustic response. However, such dyes are often not water soluble or they are cytotoxic. Here, we present a novel PEGylated sonophore based on diketopyrrolopyrrole (DPP), which overcomes these limitations and can be functionalized with desired biological recognition motifs using thiol–yne click chemistry. Proof of concept is demonstrated by functionalizing the DPP-based probe with an RGD peptide, resulting in specific binding to endothelial (HUVEC) cells and an efficient photoacoustic response.